National advisory board on diabetes mellitus: unsolved issues and new opportunities for diabetes treatment - Gagik Radikovich Galstyan (Сахарный диабет, 2014)
In June 2014, the national experts on diabetes mellitus discussed the opportunities to improve the efficacy and outcomes of diabetes treatment using the strategy of patient-oriented care in diabetes. Insulin degludec (Tresiba?) is a new basal ultra-long-acting insulin analogue with a flat, stable glucose-lowering profile, ultra-long duration of action (>=42 h) and less within-patient day-to-day variability in glucose-lowering effect compared with currently available basal insulins. In the clinical trial programme, insulin degludec showed a similar glycaemic control compared with insulin glargine using the same insulin dose, but with a lower risk of hypoglycaemia and a greater flexibility in the time of dosing on a daily basis, when needed. Thus, the use of insulin degludec in routine clinical practice provides an effective and improved treatment for type 1 and 2 diabetes. The simple algorithm titration of insulin degludec offers the opportunity to personalise treatment regimens according to the needs of each patient.